Evaluating The Effectiveness Of Strategic Merger In Syrian Public Establishments Field Study On Syrian Public Of Grain Institution-Branch Of Latakia - اسبر, لمى (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study investigated the concept of strategic merger and its application in the Syrian Grain Establishment and whether its objectives were achieved, within the Syrian government intends to carry out restructuring and mergering public institutions in order to increase its efficiency and improve its performance. In order to achieve the objectives of the study and testing the hypotheses, The researcher designed a questionnaire was distributed on a purposive sample of managers in administrative divisions and departments, which 48 questionnaires were retrieved, valid for statistical analysis. It includes items that strategically measure the effectiveness of the merger that took place in the studied institution through four perspectives of Balance Score Card: financial, learning& growth, internal processes and customer. The descriptive analytical approach was followed. And using inferential statistics through the Statistical package for social sciences SPSS. 27 to reach the results. The results revealed that the studied institution achieved some of its planned financial goals, such as reducing expenses and improving the performance of internal operations, but the cultural integration between human resources of the three merged institutions remained weak, and employees did not feel satisfied. The study recommended the need to work on :improving the efficiency of asset management, increasing the rate of return on investment, redeveloping the information systems, and taking great care of creating culture integration among the human resources of the merged institution.